Sensoriamento remoto orbital para o estudo das interações ambiente-ictiofauna em um reservatório Neotropical. - Schmitz, Marcelo Henrique (2020)
The differential distribution of productivity in reservoirs has consequences for the fish assemblage, influencing spatially in its distribution, along a longitudinal gradient. Following the hypothesis that the spatiotemporal dynamics of chlorophyll a and turbidity influence the distribution of the fish assemblage in the Sobradinho reservoir, BA, three predictions were tested: i) Whether the spatiotemporal variations of these variables, determined by digital processing of remote sensing images, follow the spatial zoning pattern described in the literature, for large reservoirs; ii) Whether with the increase in distance, in kilometers, from the collection points to the dam, there is an increase in the total abundance of fish; and iii) If, with the increase in productivity, represented by higher concentrations of chlorophyll a and turbidity, there is an increase in the abundance of fish (total or by trophic guild). The sampling was distributed in five periods, between April 2008 and July 2009, with at least one collection being carried out in each zone of the reservoir, fluvial, transition and lake, in each period. Bands 2 and 3 of scenes from the Landsat-5 satellite were selected, in which the chosen limnological variables show their peak of reflection. With the values of the collections in situ and the reflectance of the scenes, an interpolation was performed and, later, thematic maps of each of the variables were elaborated. The chlorophyll a and turbidity values of the ichthyofauna collection points were extracted from the interpolations. To analyze the existence of the longitudinal gradient, Spearman correlation analyses were performed between the value of the limnological variables and the distance from the collection point to the dam, obtained by extracting a longitudinal profile of the reservoir. To search for associations between limnological variables and ichthyofauna, Spearman's correlation analyses were performed with the value of the variables and total abundance and by trophic guilds. Also, the analyses were carried out dividing the collection points according to the reservoir area and the rainfall regime (dry and full). The Sobradinho reservoir showed a pattern of productivity zoning consistent with the typical pattern of large reservoirs. This zoning had a strong association with the distribution of fish abundance in the Sobradinho reservoir. There was an association between the abundance of fish in the lake area and the seasonal increase in productivity, with a remarkable decrease in abundance during the dry months and an increase in abundance during the floods. However, in the river zone, excess turbidity acted as a limiting factor. High values of this variable, also showing a greater flow of water, may have favored the dispersion of organisms to places of lesser environmental stress, reducing the abundance of fish in this region during floods. However, in general, the fluvial zone showed the highest abundances, exhibiting the well-known fluvial> transition> lacustrine pattern. The presence of favorable characteristics in the river zone, such as seasonal flooding and greater environmental heterogeneity, may have contributed to this result.